2021
DOI: 10.7759/cureus.20472
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Case-Based Learning in Anatomy

Abstract: In the present Competency-Based Medical Education (CBME), learning is more student-centered where the students take the responsibility for their learning. Anatomy is an important basic science that lays the foundation for clinical courses in the Bachelor of Medicine and Bachelor of Surgery (MBBS) curriculum. To make it interesting and clinically useful, several innovative teaching-learning methods like case-based learning (CBL) and problem-based learning (PBL) are introduced. The present study was taken up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…As a discipline focusing on clinical practice and rigor, clinical medicine is closely related to the whole process of patient diagnosis and treatment [ 1 ]. An excellent clinician often needs to accumulate a lot of theoretical basis and practical experience in order to make a more accurate diagnosis and treatment of patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a discipline focusing on clinical practice and rigor, clinical medicine is closely related to the whole process of patient diagnosis and treatment [ 1 ]. An excellent clinician often needs to accumulate a lot of theoretical basis and practical experience in order to make a more accurate diagnosis and treatment of patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sangam et al also cited CBL as a teaching-learning method that is more effective in promoting and maintaining knowledge. The results of their study showed that the mean scores of the CBL group were signi cantly higher than the lecture-based learning group (23).…”
Section: Discussionmentioning
confidence: 96%
“…Most previous studies reported that CBL is a powerful tool and educational strategy that improves students' , independent learning skills, and ability to prepare for exams, and is a self-directed learning approach [15,17].…”
Section: Discussionmentioning
confidence: 99%